2012
DOI: 10.1115/1.4006021
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Magnetorheological Fluids by the Discrete Element Method

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. Modeling of Magnetorheological Fluids by the Discrete Element MethodMagnetorheological (MR) fluids are fluids whose properties vary in response to an applied magnetic field. Such fluids are typically composed of microscopic iron particles ($ 1 À 20 lm diameter, 20 À 40% by volume) suspended in a carrier fluid such as mineral oil or water. MR fluids are increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The cores and shells were simulated as made of pure iron and silica respectively (Neville and Moreno-Atanasio, 2012 ; Hyde et al, 2017 ). The magnetization of the particles was set at 1/10 th of the saturation magnetization value of iron 0.228 T/μ 0 (Reitz et al, 2008 ; Kargulewicz et al, 2012 ).…”
Section: Methodology: Dem Computer Simulation Optimization Of Coated mentioning
confidence: 99%
See 1 more Smart Citation
“…The cores and shells were simulated as made of pure iron and silica respectively (Neville and Moreno-Atanasio, 2012 ; Hyde et al, 2017 ). The magnetization of the particles was set at 1/10 th of the saturation magnetization value of iron 0.228 T/μ 0 (Reitz et al, 2008 ; Kargulewicz et al, 2012 ).…”
Section: Methodology: Dem Computer Simulation Optimization Of Coated mentioning
confidence: 99%
“…Lindner et al ( 2013 ) combined DEM with FEM to determine the external magnetic field and the fluid flow around cylindrical wires. Other DEM studies focused on predicting the magnetic particle behavior during compression, shearing and breakage of magnetic chains were published by Kargulewicz et al ( 2012 ); Lagger et al ( 2015a , b ); Soda et al ( 2015 ). Ke et al ( 2017 ) coupled DEM with Lattice Boltzmann Method and Immersed Boundary Method to simulate the settling of two individual magnetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the output control performance of MRF and MRE application systems should be the best with the chosen controller under any environmental conditions. Despite the significance of the choice of an appropriate controller for MRF and MRE application systems, a full review article on the control strategies has not been reported so far, while several review articles on modeling of MR materials and dynamic modeling techniques of MR application systems have been introduced by several researchers [293][294][295][296][297][298][299][300][301][302].…”
Section: Introductionmentioning
confidence: 99%
“…Kargulewicz et al . [ 18 ] developed a discrete element algorithm to optimize aircraft ejector seat applications. Zueco and Bég [ 19 ] applied the electro-thermal network simulation code to study magneto-elastic hydrodynamic lubrication between rotating disks at generalized magnetic Reynolds numbers, as a model of conceptual spacecraft landing gear systems for Mars NASA missions.…”
Section: Introductionmentioning
confidence: 99%